Analisis Yuridis Terhadap Praktik Aborsi Akibat Pemerkosaan Kaitannya Dengan Hak Asasi Manusia - Rosnida Rosnida (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research was conducted with the aim to find out how the regulation of abortion according to health law relates to human rights and what are the factors that influence the occurrence of abortion to rape in the perspective of human rights. By using normative juridical research methods, it is concluded: 1 Rules regarding abortion in Indonesia are regulated in the Criminal Code and the Law on Health. 2. In general, the factors that influence abortion, the factor of the law itself, the sociological factor of public legal awareness, the psychological factor, and the economic factor.